Analisis Pengguna Lensa Kontak Lunak Bulanan di Optik X Daerah Mall Bintaro Xchange - Martina Ariyani; Fiandhika Ekaputra; Supriyati Supriyati; Taufik Hadi; Darmono Darmono (KOLONI, 2026)
efractive disorders such as myopia, hypermetropia, and astigmatism are still the leading causes of sharp visual impairment in the productive age population worldwide. Refractive correction efforts can be made using glasses or contact lenses. As optical technologydevelops, contact lenses are increasingly in demand because they provide a wider field of view, reduce peripheral distortion, are lessprone to fog, and provide a more aesthetically pleasing look. In addition to optical functions, the use of contact lenses is also closelyrelated to psychosocial factors, such as increased self-confidence, comfort during exercise, and ease in daily activities, making it apopular choice among adolescents and young adults. The use of contact lenses can be a barrier to the diffusion of oxygen to the surfaceof the cornea. If the oxygen supply is insufficient, corneal hypoxia can occur which triggers edema, neovascularization, and decreasedcorneal sensitivity. The purpose of this study is to systematically analyze user characteristics, monthly soft contact lens usage patternsand the type of materials and treatment fluids used. The method used in this study uses a quantitative approach with descriptiveanalysis. The conclusion of this study shows that monthly soft contact lens users use contact lenses for more than hours of use which isnot in accordance with the procedure. The lack of user understanding of the benefits of soft contact lens materials that are appropriatefor the hours of use, as well as the maintenance fluids are less known to contact lens users.